Plagiarism in Higher Education The Impact of EU-funded Research, Law, and AI on Evolving Academic Norms - Aczél-Partos Adrienn (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2025)
What qualifies as plagiarism, and how has its perception evolved over the past decades? Does the rise of digitalization and artificial intelligence redefine the concept of plagiarism, or does it merely introduce new forms of literal copying? The definition and assessment of plagiarism have undergone continuous transformation, particularly with the increasing influence of digital technologies and AI. This raises the question of whether these innovations create novel challenges in identifying and managing plagiarism or simply bring existing problems to the fore in new ways. This paper explores the multifaceted nature of plagiarism definitions, in particular in national copyright and criminal law provisions as well as EU regulations. It examines EU-funded projects conducted between 2010 and 2019 that investigated plagiarism in higher education, paying special attention to differences between faculty and student attitudes. In addition, the present paper analyses the impact of AI-based technologies, which present both new challenges to, and opportunities for detecting and preventing plagiarism. The research aims at mapping how legal and ethical approaches to plagiarism may evolve with the appearance of these technologies and to what extent the findings of past EU projects remain applicable in the current academic landscape.